The Bristol Merlin revealing the secrets of a medieval fragment - Tether, Leah ca. 20./21. Jh; Chuhan Campbell, Laura; Pohl, Benjamin 1985- (Medieval media cultures, 2021)
The discovery of seven manuscript fragments of the Old French Suite Vulgate du Merlin in a set of early printed books in the Bristol Central Library hit global headlines in 2019. This book contains a comprehensive study and accompanying transliteration of these fascinating Arthurian fragments. Beginning with an extensive contextual history, the authors reveal details of the fragments' origin, their importation to England, and their subsequent journey to a waste pile in a bookbinder's workshop, where they would be incorporated into the bindings of a four-volume edition of the works of Jean Gerson in the early sixteenth century. A full enquiry into the provenance of these host volumes sets out the possible routes from the bookbinder's workshop to their final home in Bristol Central Library. Using multi-spectral imaging to read the damaged sections of text, the authors also provide a full edition of the narrative contained in the fragments